Harnessing the ECM Microenvironment to Ameliorate Mesenchymal Stromal Cell-Based Therapy in Chronic Lung Diseases - Elowsson Rendin, Linda; Löfdahl, Anna; Kadefors, Måns; Söderlund, Zackarias; Tykesson, Emil; Rolandsson Enes, Sara; Wigén, Jenny; Westergren-Thorsson, Gunilla (Frontiers in Pharmacology, 2021)
It is known that the cell environment such as biomechanical properties and extracellular matrix (ECM) composition dictate cell behaviour including migration, proliferation, and differentiation. Important constituents of the microenvironment, including ECM molecules such as proteoglycans and glycosaminoglycans (GAGs), determine events in both embryogenesis and repair of the adult lung. Mesenchymal stromal/stem cells (MSC) have been shown to have immunomodulatory properties and may be potent actors regulating tissue remodelling and regenerative cell responses upon lung injury. Using MSC in cell-based therapy holds promise for treatment of chronic lung diseases such as idiopathic pulmonary fibrosis (IPF) and chronic obstructive pulmonary disease (COPD). However, so far clinical trials with MSCs in COPD have not had a significant impact on disease amelioration nor on IPF, where low cell survival rate and pulmonary retention time are major hurdles to overcome. Research shows that the microenvironment has a profound impact on transplanted MSCs. In our studies on acellular lung tissue slices (lung scaffolds) from IPF patients versus healthy individuals, we see a profound effect on cellular activity, where healthy cells cultured in diseased lung scaffolds adapt and produce proteins further promoting a diseased environment, whereas cells on healthy scaffolds sustain a healthy proteomic profile. Therefore, modulating the environmental context for cell-based therapy may be a potent way to improve treatment using MSCs. In this review, we will describe the importance of the microenvironment for cell-based therapy in chronic lung diseases, how MSC-ECM interactions can affect therapeutic output and describe current progress in the field of cell-based therapy.